The Bible in early transatlantic Pietism and evangelicalism - Hoselton, Ryan P.; Stievermann, Jan; Sweeney, Douglas A.; Haykin, Michael A. G. (The Pennsylvania State University Press, 2022)
Bible editions, translations, and commentaries in German Pietism / Douglas H. Shantz -- Biblical aids, editions, translations, and commentaries by dissenters, Methodists, and Church of England Evangelicals in eighteenth-century England / Isabe; Rivers -- Early modern Dutch Reformed exegesis and its Pietist-Evangelical reception / Adriaan C. Neele -- Reading the Bible : John Owen and early Evangelical "Biblicism" / Crawford Gribben -- Bible politics and early Evangelicalism : scriptural submission and resistance in noncomformist commentary / Robert E. Brown -- The Bible in early Pietist and Evangelical missions / Ryan P. Hoselton -- The Evangelical supernatural in early modern British Protestantism : Cotton Mather and Jonathan Edwards on the miracles of Jesus / Douglas A. Sweeney -- Lay appropriations and female interpretations of the Bible in German Pietism / Ruth Albrecht -- "My beloved is white and ruddy" : particular Baptist readings of the Song of songs in the long eighteenth century / Michael A. G. Haykin -- Cotton Mather, Jonathan Edwards, and the relationship between historical and spiritual exegesis in early Evangelicalism / Kenneth P. Minkema -- Reading Revelation and revelatory readings in early awakened Protestantism : a transatlantic comparison / Jan Stievermann -- "At any price give me the book of God!" : devotional intent and Bible reading for the early Evangelicals / Bruce Hindmarsh -- Spirit of the word : scripture in the lives of Evangelical and Moravian women in the New World, 1730-1830 / Benjamin M. Pietrenka and Marilyn J. Westerkamp -- Moravians and the Bible in the Atlantic world : the case of the daily watchwords in Bethlehem, PA, 1742-1745 / Peter Vogt.
Keywords: Bible -- Criticism, interpretation, etc -- History -- 18th century; Bible -- Commentaries -- History and criticism; Aufsatzsammlung; Geschichte 1650-1800; Evangelikale Bewegung; Pietismus; Biblizismus; Bibellektüre; Atlantischer Raum